Collaborative Learning in Computer Labs for Science Education: A Systematic Review - J. Mohammed Salih, Hakar; Y. Arif , Jahwar; Q. Sabri , Shaimaa (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study analyzes the use of Computer-Supported Collaborative Learning (CSCL) in computer laboratory settings for secondary school science education. The literature review evaluates the impact of collaborative methods using computer simulations, virtual experiments, and other digital technologies. The search yielded 33 relevant studies, indicating that collaborative conditions outperformed individual laboratory work in computer environments across various measures. Collaborative work in pairs or small teams has been shown to lead to better learning outcomes and expert-like reasoning patterns. Additionally, students have reported finding collaborative computer laboratory work more enjoyable, engaging, and preferable to independent work. The integration of computer-supported collaborative learning (CSCL) into science education presents opportunities to enhance students' learning experiences through interactive and collaborative approaches. This study highlights the importance of student-centered learning design, effective group dynamics, and reliable technology infrastructure for successful CSCL implementation. Additional research is required to identify the best group composition and task design, as well as the implications for effectively implementing computer-supported collaborative learning in science laboratories.